Extending the geographic range of the ensign wasp Decevania reticulata Kawada, 2007 (Hymenoptera: Evaniidae): first record in Brazil and some notes about distribution - Bezerra da Silva, Antonielson; Kawada, Ricardo; Fernandes, Daniell Rodrigo Rodrigues (Acta Biológica Paranaense, 2023)
We extend the geographic range of the ensign wasp Decevania reticulata Kawada, 2007 from Amazon rainforest and “lavrado” in Roraima and Amazon states, Brazil. Additionally, we illustrate the species and add some comments about its distribution.